Pola Asuh Orang Tua Pada Anak Usia Middle Childhood Yang Memiliki Gangguan Kepribadian - Sitti Fatimatus Zahroh; Nur Khotimah Nur Khotimah; Viedy Dimas Aditya (STAI Publisistik Thawalib Jakarta, 2022)
The purpose of this research is to describe the parenting patterns of middle childhood children who have personality disorders in Sobih Hamlet, Waru Village, Pamekasan. This type of qualitative research with a phenomenological approach. Data collection techniques are observation, documentation and interviews with parents, children, and their closest family and teachers. The analytical techniques used are data reduction, data display, and conclusion drawing/verification. The results showed: 1) the parenting style applied by the first parent was authoritarian parenting by limiting the child and giving punishment when the child made a mistake that was not in accordance with the will of the parents. The second parenting style is permissive, that is, children are given any freedom without parental supervision. 2) authoritarian parenting style applied by parents has a negative impact, namely not confident, aggressive, difficult to socialize, and has selfishness. Permissive parenting applied by parents will have an impact on learning achievement, children may become lazy and spoiled, and do not care about the learning outcomes achieved due to lack of attention from parents.